Last meal: food composition of road-killed Lacerta viridis (Reptilia: Lacertidae) from Romania - Alexandra-Roxana-Maria MAIER; Achim-Mircea CADAR; Severus-Daniel COVACIU-MARCOV (Studia Universitatis Babeș-Bolyai. Biologia)
Food composition of road-killed Lacerta viridis was studied on 41 individuals from the scientific collection of the University of Oradea, Romania. They were collected from different roads in the country between 1998-2019. All lizards had stomach contents. Although in most cases the stomach contents were partially digested, the preys could be identified at a taxonomical level comparable with the one achieved in other lizard feeding studies. The analysed L. viridis individuals had consumed 275 preys, which belong to 25 taxa, as well as inorganic elements and vegetal remains. The most important preys were Orthoptera, Araneidae and Coleoptera. The differences in lizards` food composition according to geographic origin were not significant. Our results confirm that this species food composition can be studied on road killed individuals, but also proves the uniformity of its food, at least in the Balkan Peninsula.